Recent Endoscopic Ultrasound-Related Publications With Potential to Influence Clinical Practice - Gawande, Atul; Mukewar, Shrikant; Daswani, Ravi; Bhaware, Bhushan; Mukewar, Saurabh (Journal of Digestive Endoscopy, 2021)
The field of endoscopic ultrasound (EUS) has evolved significantly over the last two decades from being a tool of only diagnostic purpose to tissue acquisition and now therapeutic potential. There have been several important publications in the field of EUS in the last few years, which had a major impact in the clinical management of various gastrointestinal disorders. In this review, we discuss four such articles that in our opinion will significantly impact the role of EUS in treating various conditions. The first article is a randomized controlled trial comparing EUS-guided gall bladder drainage with percutaneous gall bladder drainage for high-risk acute cholecystitis. The second article is a randomized controlled trial comparing EUS versus minimally invasive surgery for necrotizing pancreatitis. The third article is a novel human study of EUS-guided portal pressure measurement in patients with portal hypertension. The last article is also a randomized controlled trial evaluating the role of rapid on-site evaluation for EUS-guided fine needle biopsy in solid pancreatic lesions.
Keywords: endoscopic ultrasound; gall bladder drainage; acute necrotizing pancreatitis; lumen-apposing metal stent; portal hypertension; solid pancreatic lesion